Endoscopic Injection Therapy in Bleeding Peptic Ulcers. Low Mortality in a High Risk Population - Joaqulm Balanzó; Candid Villanueva; Jorge C Espinós; Sergio Sáinz; German Soriano; Dolors González; Xavier Rius; Jorge Puig La Calle; Francisco Vilardell (Canadian Journal of Gastroenterology)
Endoscoric injection therapy was performed in 341 patients consecutively admitted with a bleeding peptic ulcer at high risk of further hemorrhage, assessed by the presence of active arterial bleeding or a nonbleeding visible vessel at emergency endoscopy. Initial hemostasis was achieved in 111 of 119 actively bleeding patients (93%). Rebleeding ocurred in 75 cases (23%), at a mean interval of 53±52 h. A second emergency injection was a ttempted in 36 therapeutic failures, and was successful in 20 (55%). Emergency surgery was finally required in 52 patients (15%). Overall mortality was 4.9%. Major complications occurred in four patients (1.2%) (two perforations and two aspiration pneumonia); therefore, injection therapy is an effective and simple method for treating bleeding ulcers, achieving the initial control of hemorrhage in a majority of cases although the rate of further hemorrhage is not negligible and complications are not irrelevant.